2021
DOI: 10.3390/pharmaceutics13030403
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Polymer Insect Repellent Conjugate for Extended Release and Decreased Skin Permeation of Para-Menthane-3,8-Diol

Abstract: Background: We developed a novel polymer insect repellent conjugate for extended release and decreased skin permeation of the volatile insect repellent p-menthane-3,8-diol (PMD). Methods: PMD was conjugated with acryloyl chloride via an ester bond to form acryloyl–PMD, which was subsequently copolymerised with acrylic acid at varying molar ratios. Copolymer structures were characterised by 1H NMR and FT-IR, analysed by thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), molecular weights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The authors determined that the copolymer released around 45% of PMD over a period of 5 days. This had the potential to prolong repellent efficacy as well as reducing PMD associated allergic reactions since skin uptake was reduced [74]. A study by Maguranyi et al found that eucalyptus essential oils were least effective at repelling Aedes aegypti, providing only 10 min to 25 min of protection.…”
Section: Lemon Eucalyptus Oilmentioning
confidence: 99%
“…The authors determined that the copolymer released around 45% of PMD over a period of 5 days. This had the potential to prolong repellent efficacy as well as reducing PMD associated allergic reactions since skin uptake was reduced [74]. A study by Maguranyi et al found that eucalyptus essential oils were least effective at repelling Aedes aegypti, providing only 10 min to 25 min of protection.…”
Section: Lemon Eucalyptus Oilmentioning
confidence: 99%
“…The vapor barrier of picaridin disrupts the insect’s olfactory sense and taste, preventing contact . Encapsulation of repellents has been shown to enable the extended release of repellents. , For example, solid lipid nanoparticles (SLN) have a high capacity of repellent loading but require direct contact with the skin . Polymer-based encapsulations have proven to be most effective while limiting contact with the skin.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to DEET, other repellents of synthetic origin have been applied in commercial formulations, such as picaridin (icaridin, hydroxy-ethyl isobutyl piperidine carboxylate, Figure 2A) and N-acetyl-n-butyl-3-amino propionate (IR3535, Figure 2A). Currently, several natural compounds from essential oils have been also used in commercial repellent formulations due to their satisfactory repellent activity, such as the p-menthane-3, 8-diol (PMD) [18,27] (Figure 2B) and citronellal (Figure 2B) [28,29]. Some repellents act as competitive inhibitors of attractant molecules that are exhaled by the mammalian hosts.…”
Section: Introduction Repellents: Mode Of Action and Current State Of...mentioning
confidence: 99%